KEPUASAN KERJA MEMEDIASI PENGARUH PERSON-ORGANIZATION FIT TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN BBPOM DENPASAR - Krisna, Gusti Ayu; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 10 No 3 (2021)DO - 10.24843/EJMUNUD.2021.v10.i03.p03, 2021)
This research was conducted at the Center for Drug and Food Control Denpasar with 99 respondents using saturated sampling. Data collection using a questionnaire and analyzed by path analysis. The results shows Person-Organization Fit has a positive and significant effect on organizational commitment. Person-Organization Fit has a significant positive effect on Job Satisfaction. Job satisfaction has a positive and significant effect on Organizational Commitment. Job Satisfaction is able to positively mediate the influence of Person-Organization Fit on Organizational Commitment. The implication regarding unsuitable Person-Organization Fit and low Job Satisfaction which can significantly reduce Organizational Commitment, when Person-Organization Fit is appropriate, it can increase the Job Satisfaction felt by employee so that it has the potential to increase Organizational Commitment. Keywords: person-organization fit, job satisfaction, organizational commitment